Determinants of financial inclusion in Africa and OECD countries - Samuel Fiifi Eshun; Evžen Kočenda (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Using a dynamic panel data analysis, we explore the factors influencing financial inclusion in Sub-Saharan Africa (SSA) and countries belonging to the Organization for Economic Co-operation and Development (OECD). We employ the System Generalized Method of Moments (GMM) estimator and assess 31 SSA and 38 OECD countries from 2000-2021. We found that the differences in trade openness, banks' efficiency, income, and remittances are some macro-level factors that explain the variation in financial inclusion levels. We highlight the importance of quality literacy policies, trade improvement with restrictions on cross-border capital flows, and a more efficient financial system to promote financial inclusion.
Keywords: C23; E44; F65; G21; O16; O57; 330; Financial Inclusion; Financial Inclusion Index; Sub-Saharan Africa (SSA); Organization for Economic Co-operation and Development (OECD); System Generalized Methods of Moments (GMM)